Analysis of the need to implement dstu ISO/IEC 80079-34 - Тіхенко, Валентин Миколайович; Меженков, Костянтин Володимирович; Антоненко, Тетяна Сергіївна (Eastern-European Journal of Enterprise Technologies, 2015)
Taking into account the adaptation of Ukrainian technical regulations to European Directives, there is the need for timely implementation of harmonized international and European standards, participation of technical committees and specialized organizations in budget programs for standardization. The paper considers the actual problem of the lack of the state standard for quality management system of explosion-proof equipment manufacturer. As a result of the study, the scope of international standard was presented, the main differences in ISO/IEC 80079-34 and DSTU ISO 9001:2009 were highlighted, the use of the standard as an evidence base in assessing conformity with the Technical regulation was justified. The results have practical value and can be used for further adaptation of the Ukrainian technical regulation system to European requirements. The findings presented in the paper are of interest to government agencies, technical committees and organizations that deal with the above problem.